Assessing Willingness to Pay for IVF Among Infertile Women in Greece: A Single‐Center Case Study - Christos Ntais; Mary Artsita; Michael A. Talias; John Fanourgiakis; Nikolaos Kontodimopoulos (Health Science Reports)
ABSTRACT Background and Aims In recent years, In Vitro fertilization (IVF) science has grown by leaps and bounds in the field of assisted reproduction, helping millions of couples worldwide. The aim of this study is to examine the extent to which infertile women are willing to pay for IVF services in Greece. Methods Through the distribution of questionnaires, willingness to pay (WTP) is recorded according to IVF success rates, and the relationship between WTP and the respondents' demographic characteristics is analyzed. Subjects were divided into two groups according to age and were given a hypothetical scenario, according to the contingent valuation approach. Results The majority of women were reluctant to pay the amount of money corresponding to the average cost of an IVF cycle in Greece. In particular, participants replied that the amount they would be willing to pay is only one‐third of the indicative amount of €6000. Moreover, WTP is not influenced by the professional status or educational level of the participating women. Conclusion This study highlights the financial barriers many couples face when pursuing assisted reproduction. If the average cost of IVF were lower, infertile women would be willing to undergo more IVF cycles if necessary. This finding has important implications for the valuation of IVF services and the development of pricing policies to enhance affordability and accessibility. Policymakers must consider reforms that balance the cost of IVF with its societal benefits. By incorporating this aspect into pricing and policy decisions, Greece can improve the accessibility of IVF services and ensure equitable treatment opportunities for all concerned individuals.